New Advances in the Study of Regulation of Tomato Flowering-Related Genes Using Biotechnological Approaches - Denis Baranov; Sergey Dolgov; Vadim Timerbaev (Plants, 2024)
The tomato is a convenient object for studying reproductive processes, which has become a classic. Such complex processes as flowering and fruit setting require an understanding of the fundamental principles of molecular interaction, the structures of genes and proteins, the construction of signaling pathways for transcription regulation, including the synchronous actions of cis-regulatory elements (promoter and enhancer), trans-regulatory elements (transcription factors and regulatory RNAs), and transposable elements and epigenetic regulators (DNA methylation and acetylation, chromatin structure). Here, we discuss the current state of research on tomatoes (2017–2023) devoted to studying the function of genes that regulate flowering and signal regulation systems using genome-editing technologies, RNA interference gene silencing, and gene overexpression, including heterologous expression. Although the central candidate genes for these regulatory components have been identified, a complete picture of their relationship has yet to be formed. Therefore, this review summarizes the latest achievements related to studying the processes of flowering and fruit set. This work attempts to display the gene interaction scheme to better understand the events under consideration.